Rekonstruksi Konsep Pendidikan Agama Islam Berbasis Etika Spiritual: Studi Kritis atas Pemikiran Pendidikan al-Ghazali - Irawan, Edo Feri; Rohman, Fathur (IQRO: Journal of Islamic Education, 2025)
This article aims to reconstruct the concept of Islamic Religious Education (IRE) based on spiritual ethics through a critical study of al-Ghazali’s educational thought. The background of this research lies in the concern over the moral crisis and the loss of spiritual orientation in modern education, which tends to emphasize cognitive aspects alone. This study employs a qualitative descriptive approach using library research methods by examining al-Ghazali’s primary works such as Iḥyāʾ ʿUlūm al-Dīn, al-Munqidz min al-Ḍalāl, and Miʿyār al-ʿIlm. Data were analyzed critically using content analysis and philosophical interpretation to explore educational values from a Sufi perspective. The hypothesis proposed is that Islamic education becomes more meaningful and effective when rooted in spiritual ethics. The findings indicate that al-Ghazali’s concept of spiritual ethics is not only normative but also practical, providing an integrative foundation that connects intellectual, moral, and transcendental dimensions. This reconstruction offers a more holistic, transformative, and contextually relevant paradigm for Islamic education today.